Scintillation studies of Bi4Ge3O12 (BGO) down to a temperature of 6 K - Gironnet, J; Mikhailik, V; Kraus, H; de Marcillac, P; Coron, N (2008)
The scintillation light response and the decay time constant of Bi4Ge3O12 (BGO) were measured down to a temperature of 6 K using a multi-photon counting technique. The light response of BGO was confirmed to be temperature independent below 100 K and an estimate of the light yield was made, giving a value of 23,700±2600 ph/MeV. The temperature dependence of the scintillation decay time constant is interpreted using a simple three-level model for the emission centre which agrees well with the experimental data over the temperature range investigated. © 2008 Elsevier B.V. All rights reserved.